Moluscos da planície de inundação do alto rio Paraná (Brasil) e a potencialidade como primeiros hospedeiros intermediários de digenéticos. - Souza, Geza Thais Rangel e (2004)
This paper reports the distribution and seasonality of the species of snails intermediate hosts of digenean trematodes, and provides information about the possible infections of diplostomidae in this community, in lentic environments in the flood plain of the High Parana River. They were collected and analyzed 10 species of molluscs, which only Biomphalaria pelegrina was characterized as a potential host for Diplostomidae. There was clear seasonality in the density and abundance of shellfish, correlated significantly with the water temperature, and the highest values were observed between the months of November 2002 to February 2003. Found 32 cercariae of Hysteromorpha triloba in March 2003.